The Effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) on Self-Compassion and Defense Mechanisms in Individuals with Depression - Soufi Amlashi, Rasa; Shomali Oskoei, Arezoo; Mirzaei, Khalil (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: The aim of the present study was to determine the effectiveness of Intensive Short-Term Dynamic Psychotherapy (ISTDP) on self-compassion and defense mechanisms in individuals with depression.Methods and Materials:  The research method was quasi-experimental with a pretest-posttest-follow-up design and a control group. The statistical population of this study included all individuals with mild depression who referred to healthcare centers in districts four and six of Tehran during the spring and summer of 2023. Using convenience sampling and inclusion/exclusion criteria, 30 individuals were selected and randomly assigned to the intervention and control groups. Participants responded to the Self-Compassion Scale (Neff, 2003) and the Defense Style Questionnaire-40 (Andrews et al., 1993) for pretest, posttest, and follow-up assessments. After the implementation of ISTDP for the experimental group, the data were analyzed using repeated measures ANOVA.Findings: The results indicated that ISTDP increases self-compassion in individuals with depression. Moreover, ISTDP increases the use of mature defense mechanisms and decreases the use of immature and neurotic defense mechanisms in individuals with depression.Conclusion:  In conclusion, Intensive Short-Term Dynamic Psychotherapy (ISTDP) effectively increases self-compassion and enhances the use of mature defense mechanisms while reducing the use of immature and neurotic defenses in individuals with depression. These findings suggest that ISTDP can be a valuable therapeutic approach for improving emotional regulation and reducing depressive symptoms through deeper emotional integration and resolution of unconscious conflicts.